2013
DOI: 10.22621/cfn.v127i3.1488
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of American Crows (<em>Corvus brachyrhynchos</em>) when encountering an oncoming vehicle

Abstract: mukherjee, Shomen, jayanti ray-mukherjee, and robin Sarabia. 2013. Behaviour of American Crows (Corvus brachyrhynchos) when encountering an oncoming vehicle. the Canadian Field-naturalist 127(3): 229-233.A carrion feeder attempting to forage on a road benefits greatly from an appropriate response to vehicular traffic. in this observational study, we tested the ability of American Crows (Corvus brachyrhynchos) to judge the behaviour of fast-moving vehicles and avoid collision on a narrow road. unsurprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Crows in the same lane as cars often walk to the opposite lane. Therefore, crows can detect directionality of an oncoming car implying that crows understand the behaviour of vehicular traffic [8]. These observations are consistent with behavioural adjustment to traffic in free-living animals.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Crows in the same lane as cars often walk to the opposite lane. Therefore, crows can detect directionality of an oncoming car implying that crows understand the behaviour of vehicular traffic [8]. These observations are consistent with behavioural adjustment to traffic in free-living animals.…”
Section: Introductionsupporting
confidence: 77%
“…This is an exceedingly small mortality that is unlikely to have a significant impact on micro-evolution even if we consider the fact that such mortality is not distributed evenly in space and time. A cognitive study of behaviour in birds in relation to the risk of death caused by traffic has shown adjustment in risk-taking behaviour of individual birds to speed limits [7]; also crows adjust their choice of lane use according to that used by drivers and to the specific behaviour of drivers [8]. Such behavioural adjustment of individual birds to the specifics of traffic is likely to have an underlying neural substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies across taxa have shown that FID (not necessarily the likelihood of initiating escape) is generally longer when predators (including humans) approach directly versus tangentially (Burger and Gochfeld , ; Stankowich and Blumstein ; Stankowich and Coss ; Møller and Tryjanowski ). Also, there is evidence for bird learning with respect to risk associated with the type of approach by ground‐based vehicles (Legagneux and Ducatez , Mukherjee et al , DeVault et al ). Despite positive effects on FID and the potential for learning, it is intuitive that birds using taxiways and runways will be exposed more frequently to direct aircraft approach, potentially enhancing strike risk.…”
Section: Discussionmentioning
confidence: 99%
“…Also, birds have been shown to adjust their FID based on experience with vehicle approach, road section and posted speed, not necessarily realized or actual vehicle speed (Legagneux & Ducatez, 2013). Mukherjee, Ray-Mukherjee & Sarabia (2013) observed that American crows ( Corvus brachyrhynchos ) feeding on carrion in the same road lane as an approaching vehicle would fly or walk to the opposite lane at some point, whereas individuals in the opposite lane chose to remain in place. Finally, Nordell, Wellicome & Bayne (2017) reported that ferruginous hawks ( Buteo regalis ) that experienced vehicle approach on low-traffic volume access roads showed greater FIDs than birds exposed to vehicle approach on highways and other high-traffic volume roads, indicating possible habituation.…”
Section: Discussionmentioning
confidence: 99%